BACTERIAL FLORA ASSOCIATED WITH DISEASED FISH AND THEIR ANTIBIOGRAM - Abraham, T. Jawahar; Sasmal, Debasis; Banerjee, Tirthankar (Journal of Indian Fisheries Association, 2015)
Bacterial flora associated with tail rot I fin rot of Carassius auratus,Xiphophorus helleri and hemorrhagic ulcers of Clarias spp were studied.Sensitivity pattern of 33 isolates comprising Aeromonas spp, Pseudomonasspp and Gram-positive rods from diseased C. auratus, X. helleri and Clariasspp were screened against six broad-spectrum antibiotics viz. ciprofloxacin,chloramphenicol, co-trimoxazole, gentamycin, nitro-furantoin andoxytetracycline. Ciprofloxacin was the most effective in inhibiting bacteriaat 0.05 - 0.10 p.g/ml level. About 44% of Pseudomonas spp. were resistant tonitrofurantoin. Resistance to oxytetracycline was seen in 27% of Aeromonasspp Gram-positive rods were comparatively more resistant to antibiotics.The multiple antibiotic resistance was seen in 21% of the bacterial isolatesof diseased fish.Key words: Fish pathogens, Antibiogram